The Role Of Social Media Marketing To Improve The Brand Image Of Jawa Timur Park 3 (Case Study Of Jatim Park Halloween Season Event) - Nada Samira; Nurul Asfiah; Immanuel Mu'ammal (International Journal of Entrepreneurship and Tourism, 2024)
Digital developments and the emergence of social media have drastically changed the way people interact and communicate. Social media has become an effective tool for companies in disseminating promotional content, interacting with consumers, and building a strong brand image. Therefore, this research focuses on social media which can be used strategically to improve the brand image of Jawa Timur Park 3. The type of research used in this research is descriptive qualitative with snowball sampling techniques. The data collection methods for this research are interviews, observation and documentation. This research shows that the role of social media marketing has a significant impact in increasing brand image, follower engagement and positive perceptions of Jawa Timur Park 3.